Knowledge and Attitude of Sidoarjo Communities About The Prevention of Covid-19 Transmission - Setyawati, Irni; Utami, Kusniyati; Suprayitna, Marthilda (Universitas Qamarul Huda Badaruddin, 2020)
The world is currently being hit by an outbreak of a pandemic virus resembling an upper respiratory tract infection (URI/URTI) whose cause is still unknown. As of July 27, 2020 the number of Covid-19 cases in East Java was 20,539 positive confirmed cases, 12,318 people were cured, and 1,589 people were declared dead (Indonesian Covid-19 acceleration task force, 2020). Covid-19 positive cases in Sidoarjo, up to July 27, 2020 there were 3,041 positive people confirmed, 1,745 people were cured, and 180 people were declared dead (Department of Communication and Information of Sidoarjo Regency, 2020). The aim was to identify the knowledge and attitudes of the Sidoarjo people about the prevention of Covid-19 transmission.The design of this study is a descriptive survey with cross sectional approach. Respondents are male or female aged more than the same as 20 years who live in Sidoarjo regency. Data collection using a Google-based questionnaire form distributed through WhatsApp on 15-18 July 2020 to 18 districts. The questionnaire received 124 responses from 13 districts.Most respondents had good knowledge about the prevention of Covid-19 transmission as much as 94.4% but the majority of respondents had a negative attitude of 54.8%. It is expected that education by the village / sub-district / district government will be maximized by involving religious leaders and community leaders from the RT / RW / village / kelurahan level about efforts to prevent Covid-19 transmission in Sidoarjo. Keywords: transmission prevention, Covid-19, Sidoarjo